PENGARUH RETURN ON INVESTMENT (ROI), CASH RATION, DEBT TOTAL ASSET, EARNING PER SHARE (EPS) DAN SIZE ATAS DIVIDEN KAS (STUDI PADA EMITEN MANUFAKTUR DI BURSA EFEK JAKARTA) - jen, Surya (Jurnal Akuntansi Muhammadiyah, 2011)
The objective of this research is to examine and analyze the influence of return on investment (ROI), cash ratio, current ratio, debt to total asset (DTA), earning pershare (EPS), and size as independent variabel to dividen kast as dependent variabel both simultaneously an partially in manufacturing companies listed in Jakarta stock exchange (JSX). Observation periods from 2001 until 2005. The type of research used in verification research or research to verify hypothesis with simple random sampling. The object of population are manufacturing industries which listed in Jakarta Stock Exchange (JSX)  that it’s financial statement has information about return on investment (ROI,)  cash ratio, current ratio, debt to total asset (DTA), earning pershare (EPS), size and paid to dividen kast. The research samples 21 manufacturing corporation. To aimed influence of independent variable to dependent variable both simultaneously and partially use multiple regression. Result of this research show that; (1) ROI has no significant influence on dividen kast, (2) cash ratio has no significant influence on dividen kast, (3) current ratio has significant influence on dividen kast, (4) DTA has no significant influence on dividen kast, (5) EPS has a significant influence on dividen kast,(6) size has no significant influence on dividen kast, (7) simultaneously ROI, Cash ratio, current ratio, DTA, EPS and size has a significant (72%) influence on dividen kast. Keywords: return oninvestment (ROI), Cash ratio, current ratio, debt to total asset (DTA),earning per share ( EPS), size and dividen kast. DAFTAR PUSTAKA   Algifari (2000), Analisis Regresi: Teori, Kasus dan Solusi, Edisi 2, BPFE,Yogyakarta. Bringham F. Eugene (2000), Manajemen Keuangan , Edisi 8, Erlangga. Edi  Susanto (2001). “  Analisis Faktor- Faktor yang mempengaruhi Kebijakan Dividen Di BEJ Periode 1999”. Eduardus Tandelilin, Analisis Investasi dan Manajemen Portofolio, BPFE, Yogyakarta. Erich. A. Helfert, Analisis Laporan Keuangan,  Edisi7, Erlangga, Jakarta,1993. Indonesian Capital Market Directory 2001 Indonesian Capital Market Directory 2003 Indonesian Capital Market Directory 2004 Jogiyanto,  Teori  Portofolio  dan  Analisis  Investasi,  BPFE  UGM            , Jogjakarta,1998. Mutamimah dan Sulistyo. (2000).”Analisis Faktor-Faktor yang mempengaruhi Dividen Per Share Perusahaan-Perusahaan yang Go Public di Bursa Efek Jakarta”. Niniek  Dwi  Puspitowati (1998),  Pengaruh  Pengumuman  Pembagian  Dividen Tunai  Terhadap  Aktivitas  Volume  Perdagangan  Saham  di  BEJ,  Tesis, Universitas Gajah Mada, Yogyakarta. Robbert Ang (1997), Buku Pintar: Pasar Modal Indonesia, Mediasoft Indonesia. Sawidji  Widoadmodjo (1996),  Cara  Sehat  Investasi  di  Pasar  Modal,  PT Jurnalindo Aksara Grafika, Jakarta. Sri Rahayu (2004), Belajar Mudah SPSS Versi 11.05, Alfabeta, Bandung. Sritua  Arief,  Metodologi  Penelitian  Ekonomi,  Penerbit  Universitas Indonesia, Jakarta, 1993. Suad Husnan (1994), Dasar Teori Portofolio dan Analisis Sekuritas, Edisi  2, AMP YKPN, Yogyakarta. Sugiyono, Statistika Untuk Penelitian, Alfabeta, Bandung,2001. Sumarmo (1990), Pengantar tentang Pasar Modal di Indonesia, Penerbit Balai Aksara, Yudistira dan Pustaka Saadiyah. Sunarto dan Andi Kartika, Analisis Faktor- Faktor yang mempengaruhi Dividen Kas di BEJ, Jurnal Bisnis dan Ekonomi, Vol. 10, No.1:67-82, 2003. Tri  Harsini  Wahyuningsih,  Dividen  Cut: Satu  Alternatif  Dalam Kebijakan Dividen, Jurnal Bisnis dan Ekonomi, Vol 10, 2000. Yuniningsih, Interdependensi Antara Kebijakan Dividen Payout Ratio, Financial  Leverage,  dan  Investasi  pada  Perusahaan  manufaktur  yang Listed di Burs Efek Jakarta, Jurnal Bisnis dan Ekonomi, Vol. 9, No.2: 164-182, 2001.